The relationship between number of retail-credit accounts and response rates - Y. Jordaan; T. G. Kotzé; H. Louw (South African Journal of Business Management, 2004)
In South Africa, some of the bigger credit Issuers operating in the direct marketing environment, specifically non-bank, personal finance companies, have complained that they are not seeing the return-on-investment they have come to expect from their direct mail campaigns, due to poor direct mail response rates. Low response rates have been encountered even though the market segment in which these companies are operating, has shown growing demand. With an increase in mailing costs and fierce competition in the direct marketing industry, lenders are constantly looking for ways to improve the effectiveness and profitability of their mailing campaigns. The approach followed was to analyse the response rate of a mailing campaign, and through regression analysis, determine the relationship between the number of active retail credit accounts held and response rates. This was done against the backdrop of segmentation opportunities and an increasingly credit-active South African population. The results indicate that, in the personal finance and loan marketing environment, there is a positive linear relationship between the number of active retail accounts held by prospective clients and the response rates to credit-related marketing offers. Finally, the implications for direct marketing companies are discussed, limitations presented and future research opportunities outlined.
Keywords: 650